SAT0225 Screening for Pulmonary Arterial Hypertension in Systemic Sclerosis Patients: Single Center Real-Life Performance of The Detect Algorithm. (15th July 2016) - De Nard, F.; Codullo, V.; Grosso, V.; Gallarati, A.; Ghio, S.; Scelsi, L.; Raineri, C.; Caporali, R.; Montecucco, C.
Abstract : Background: A new algorithm for early detection of PAH in Systemic Sclerosis (SSc) patients has been recently developed (1). However, the cost-effectiveness of this strategy has not yet been defined in a real-life setting. Objectives: The aim of this study was to compare two methods of PAH screening among SSc patients for the referral to invasive tests (right heart catheterization (RHC)) in a single PH referral center. Methods: Patients with SSc according to the ACR/EULAR 2013 classification criteria were enrolled in the study and prospectively followed in a Scleroderma Unit of a University Hospital which is also a PH referral center between Jan 2015 and Jan 2016 with at least 6-monthly visits. According to the ESC/ERS 2015 guidelines (2), annual screening with echocardiography, DLCO, ECG and serum biomarkers (including urate and NT-proBNP) was performed. Patients satisfying the two-steps DETECT score and/or with echocardiographically estimated Pulmonary Arterial Systolic Pressure (PASP) ≥45 mmHg or between 35–45 mmHg with unexplained dyspnea (3) were referred to an expert cardiologist to undergo RHC. Results: Three-hundred patients with a diagnosis of SSc were screened and 39 patients (13%) met the criteria for the application of the DETECT algorithm (disease duration >3 years, DLCO <60%). The male:female ratio was 1:12; 16 patients (41%) were positive for anticentromere antibodies; 14 patients showed cutaneous teleangectasias (26%); 33 patients (85%) were classified as limited SSc, 4 (10%) as diffuse SSc and 2 as SSc without skin involvement (5%). For 2 of them (5%), STEP 1 score was not calculated due to missing serum biomarkers. Among the remaining 37 patients, 2 (5%) had a STEP 1 score <300; and 35 (95%) showed a STEP 1 score ≥300. Among the latter, for 11 (31%) echocardiographic measures for the calculation of the STEP 2 score could not be derived. In 7/24 (29%) the STEP 2 score was <35 while in 17/24 (71%) ≥35, thus needing referral to RHC according to the DETECT algorithm. In the same 39-patients group, 12 (31%) satisfied the ItinerAir criteria for RHC (p=0, 0019, chi-squared). Conclusions: Our results indicate that the feasibility in clinical practice of both PAH screening methods strongly depends on the performance of a correct echocardiographic screening, with a complete assessment and quantification of right heart parameters, which often lacks in outpatient practice. In addition, applying the DETECT algorithm, a larger number of patients should be sent to RHC than those identified by solely echocardiographic parameters. Further observational studies are needed to define the real-life sensivity and cost-effectiveness of this new algorithm. References: Coghlan JG et al, Ann Rheum Dis 2014. Galiè N et al, Eur Respir J 2015. Hachulla E et al, Arthritis Rheum 2005. Disclosure of Interest: None declared